An activator-induced quencher-detachment-based turn-on probe with a cationic substrate moiety for acetylcholinesterase. Issue 10 (7th December 2021) - Oe, Masahiro; Miki, Koji; Masuda, Akito; Nogita, Kohei; Ohe, Kouichi
Abstract : A choline ester-grafted turn-on fluorescence probe for acetylcholine esterase (AChE) was developed based on fine-tuned activator-induced quencher-detachment. Abstract : We report a choline ester-grafted turn-on fluorescence probe to detect acetylcholinesterase (AChE) in living cells. The AChE-mediated hydrolysis of the choline ester moiety producing carboxylate initiates the activation of the Cy5 fluorophore quenched by an intramolecular nucleophilic mercapto group. The probe has the advantages of high AChE affinity and low cytotoxicity.